Effect of Postharvest Application of Putrescine in Increasing Storage Life and Quality Attributes in Kiwifruit (Actinidia deliciosa cv. Hayward) - Z. Roohi; M. R. Asghari; Y. Rasmi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
Application of polyamines has been reported to improve shelf life in different fruits. In this research the effect of different concentrations of putrescine with hot water on postharvest life of kiwifruit (Actinidia deliciosa cv. Hayward) at 0 ± 0.5°C was studied. Fruits were treated with putrescine (0, 1 and 2 mmol/L) and stored for 16 weeks. Fruit quality attributes assessment including firmness, soluble solid content, titratable acidity, ascorbic acid and antioxidant capacity were determined after 8 and 16 weeks of cold storage. Putrescine treatment had significant effect on firmness, titratable acidity, ascorbic acid and antioxidant capacity, but had no significant effect on soluble solid content. After 8 and 16 weeks the highest firmness was for 2mol/ L putrescine treatment. After 8 weeks the highest titratable acidity and ascorbic acid content were observed with 2mol/ L putrescine treatment and after 16 weeks were observed with 1mol/ L putrescine treatment. Putrescine treatment showed significant effect on antioxidant capacity in both measurements. The results revealed that kiwifruit storage life could be extended by putrescine treatment due, apparently, to its effect on delaying the ripenıng and senescence processes. Putrescine application in combination with hot water can be a suitable substitute for chemical post harvest treatment in kiwifruit.